Antibacterial and cytotoxic properties of esterified α- lactalbumin and β-lactoglobulin - Hossam S. El-Beltagi; Eman Ibrahem; Hayfa Habes Almutairi; Hoda A. S. Farag; Wael F. Shehata; Hefnawy Mansour; Mahmoud Sitohy; Ali Osman (Journal of Taibah University for Science)
[Formula: see text]-Lactalbumin ([Formula: see text]-La) or [Formula: see text]-lactoglobulin ([Formula: see text]-Lg) were esterified with methanol. Native proteins and their methylated esters (Est. [Formula: see text]-La and Est. [Formula: see text]-Lg) were tested for their antibacterial and cytotoxic properties. Esterification extents for Est. [Formula: see text]-La and Est. [Formula: see text]-Lg were 92% and 88%, with isoelectric points at pH 8 and 10, respectively. The Est. [Formula: see text]-La and Est. [Formula: see text]-Lg were more inhibiting the growth of pathogenic bacteria compared to the corresponding native proteins. The impact of esterified [Formula: see text]-La and [Formula: see text]-Lg on MCF-7, A549, and Caco-2 cell lines was assessed and revealed that the concentration inhibiting 50% cellular growth (IC50) for Est. [Formula: see text]-La recorded 107.93 µg/mL against MCF-7, 616.44 µg/mL against A-549, and 388.23 µg/mL against Caco2. In parallel, Est. [Formula: see text]-Lg achieved IC50 at 101.35, 420.84, and 234.16 µg/mL, against MCF-7, A-549, and Caco2, respectively. Esterified proteins may serve as therapeutic antimicrobial agents against pathogenic bacteria and cytotoxic agents against specific cancer cells.